Epigenetic Regulation of Genomic Stability by Vitamin C - Brabson, John P.; Leesang, Tiffany; Mohammad, Sofia; Cimmino, Luisa (Frontiers in Genetics, 2021)
DNA methylation plays an important role in the maintenance of genomic stability. Ten-eleven translocation proteins (TETs) are a family of iron (Fe2+) and -KG -dependent dioxygenases that regulate DNA methylation levels by oxidizing 5-methylcystosine (5mC) to generate 5-hydroxymethylcytosine (5hmC), 5-formylcytosine (5fC), and 5-carboxylcytosine (5caC). These oxidized methylcytosines promote passive demethylation upon DNA replication, or active DNA demethylation, by triggering base excision repair and replacement of 5fC and 5caC with an unmethylated cytosine. Several studies over the last decade have shown that loss of TET function leads to DNA hypermethylation and increased genomic instability. Vitamin C, a cofactor of TET enzymes, increases 5hmC formation and promotes DNA demethylation, suggesting that this essential vitamin, in addition to its antioxidant properties, can also directly influence genomic stability. This review will highlight the functional role of DNA methylation, TET activity and vitamin C, in the crosstalk between DNA methylation and DNA repair.